Polyols from recycled poly(ethylene terephthalate) flakes and rapeseed oil for polyurethane foams - Paberza, A.; Fridrihsone-Girone, A.; Abolins, A.; Cabulis, U. (Polimery, 2015)
Bio/recycled polyols from rapeseed oil (RO) and poly(ethylene terephthalate) (PET) were prepared using a continuous, two-step synthesis method. The bio/recycled polyol properties were compared to RO and commercially available PET based polyols. Rigid polyurethane foams with a unified apparent density of 40—45 kg/m3 were prepared from these polyols. The thermal conductivity, thermal properties, water absorption and mechanical properties of foams were tested. The results indicated that the RO/PET polyols can be successfully used for preparing polyurethane foams as energy efficient thermal insulation material.